find the sum of all the terms of the arthimetic squance 7,13,19,…,61​

Question

find the sum of all the terms of the arthimetic squance 7,13,19,…,61​

in progress 0
Rose 2 weeks 2021-11-15T04:41:58+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-15T04:43:00+00:00

    Answer:

    plz FOLLOW me...

    plz BRAINLIEST me...

    Step-by-step explanation:

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)d

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore,

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)33=(n-1)

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)33=(n-1)n=33+1=34

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)33=(n-1)n=33+1=34•°• there are 34 terms in the given Arithmetic progression 7,13,19…..205.

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)33=(n-1)n=33+1=34•°• there are 34 terms in the given Arithmetic progression 7,13,19…..205.☘️THANK YOU!☘️

    ❄️❄️❄️❄️❄️❄️❄️❄️❄️❄️let a be the 1st term.Therefore, a=7.2nd term =a+d 7+d=13d=13-7=6d=6.aⁿ=a+(n-1)daⁿ=7+(n-1)6w.k.t,aⁿ=205therefore, 205=7+(n-1)6205-7=(n-1)6198=(n-1)6198/6=(n-1)33=(n-1)n=33+1=34•°• there are 34 terms in the given Arithmetic progression 7,13,19…..205.☘️THANK YOU!☘️ALL THE BEST..☺️

    0
    2021-11-15T04:43:23+00:00

    Answer:

    answer for the given problem is given

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )